Analysis of Phytochemical Compounds and Antioxidant Activity From Non-Polar to Polar Solvent Extracts In Several Types of “Basa Genep” Constituent Spices - Singapurwa, Ni Made Ayu Suardani; Candra, I Putu; Semariyani, A.A. Made (Indonesian Food Science and Technology Journal, 2024)
"Basa genep" is the main spice Balinese people use to process traditional cuisine. This study examines phytochemical compounds and antioxidant activity in extracts of several “Basa genep” constituent spices extracted with solvents with different polarity levels. The design used is a completely random design of 1 factor consisting of 6 treatments: ethyl acetate solvent, hexane, acetone, dichloromethane, ethanol, and methanol. Based on the results of the study, it was found that the constituent spices of "Basa genep", namely ginger, kaemfiera, galangal, turmeric, bird’s eye chilli, red chilli, onion, and garlic extracted with solvents with different levels of polarity contain phytochemical compounds. The treatment of different types of solvents has a significant effect on the extract's phytochemical levels and antioxidant activity. The highest antioxidant activity is obtained in polar solvents, dichloromethane, acetone, and methanol. In ginger, kaemfiera, Turmeric, and garlic extracts, the highest IC50 values were obtained in dichloromethane solvent types with IC50 values of 25,027 ppm (powerful antioxidants), 93,643 ppm (potent antioxidants), 24,467 ppm (powerful antioxidants), and 288,437 ppm (fragile antioxidants). In Galangal, the highest IC50 (Inhibition Concentration 50%) value was obtained in acetone extract with an IC50 value of 82.863 ppm (potent antioxidant). In bird’s eye chilli and red chilli, the highest IC50 value was obtained in methanol extract with IC50 values of 108,088 ppm (medium antioxidant) and 274,427 ppm (very weak antioxidant), respectively.